2019
DOI: 10.36478/jeasci.2020.826.829
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Accelerometer Sensor and Gyroscope Sensor in IMU Sensors on Motion Capture

Abstract: IMU is electronic devices that used on specific body, angular rate and sometimes magnetic fields surround the body, use combination of accelerometer sensor and gyroscopes sensor, sometimes magnetometer to but IMU usually just using accelerometer and gyroscope sensor. IMU Sensor usually used on aircraft maneuver include Unmanned Aerial Vehicles (UAV) and space aircraft include landers and it's satellite. Accelerometer is an automatic tool for measuring acceleration, detecting and measuring vibration (vibration)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 3 publications
0
19
0
6
Order By: Relevance
“…An accelerometer is a sensor for accurately measuring applied acceleration [ 49 ]. Typically, an accelerometer uses three perpendicular axes, commonly referred to as x, y and z.…”
Section: Emerging Techniques For Jia Monitoring and Diagnosismentioning
confidence: 99%
“…An accelerometer is a sensor for accurately measuring applied acceleration [ 49 ]. Typically, an accelerometer uses three perpendicular axes, commonly referred to as x, y and z.…”
Section: Emerging Techniques For Jia Monitoring and Diagnosismentioning
confidence: 99%
“…At the same time, with the increasing proliferation and popularity of human skeletal capture devices i.e. Kinect [9], accelerometers-based [10], webcam-based [20], etc., researchers have also focused on the problem of recognition of actions based on skeleton analysis [21], [22]. And more recently, research community has shown interest in the recognition of expression based on body movements [23].…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, if facial expression recognition was widely studied [6], [7], body expression recognition is still an emerging area. Furthermore, with the growth and easy access of devices that track 3-dimensional body, like the Kinect [8], [9] or accelerometer [10] based motion capture system, different applications will emerge based on body expression recognition. Our assumption is that many applications would benefit from the ability to understand human emotional state in order to provide more natural interaction, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akselerometer menangkap informasi kecepatan pada sumbu x, y dan z (3-axis). Sedangkan giroskop digunakan untuk menangkap perubahan orientasi atau perubahan kecepatan rotasi yang disebut dengan roll untuk sumbu x, pitch untuk sumbu y, dan yaw untuk sumbu z [11]. Visualisasi rotasi pada masing-masing sumbu dapat dilihat pada Gambar 1.…”
unclassified